2019
DOI: 10.37311/jnj.v1i2.2425
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penyeluhan Terhadap Tingkat Pengetahuan Masyarakat Menghadapi Bencana Banjir

Abstract: Banjir merupakan salah satu bencana yang sering terjadi di Gorontalo. Pada tahun 2013-2016 Gorontalo mengalami 56 kejadian bencana banjir. Penelitian ini bertujuan untuk menganalisis pengaruh penyuluhan terhadap tingkat pengetahuan masyarakat menghadapi bencana banjir di Desa Permata Kabupaten Boalemo Provinsi Gorontalo. Jenis penelitian yang digunakan dalam penelitian ini adalah Pre-Experimental design dengan jenis rancangan One Group Pretest-posttest design. Populasi dalam penelitian ini sebanyak 140 orang k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Health education increases knowledge, changes attitudes and behaviour, and enhances the surrounding environment (physical and non-physical) to maintain and improve health with full awareness (Pakpahan et al, 2021). The results of outreach activities in Permata Village, Boalemo Regency, Gorontalo Province showed that before being given counselling, the level of community knowledge was categorized as sufficient; after being given counselling, the level of community knowledge was categorized as good and showed the effect of counselling of community knowledge about flood disaster preparedness (Yusuf & Mangile, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Health education increases knowledge, changes attitudes and behaviour, and enhances the surrounding environment (physical and non-physical) to maintain and improve health with full awareness (Pakpahan et al, 2021). The results of outreach activities in Permata Village, Boalemo Regency, Gorontalo Province showed that before being given counselling, the level of community knowledge was categorized as sufficient; after being given counselling, the level of community knowledge was categorized as good and showed the effect of counselling of community knowledge about flood disaster preparedness (Yusuf & Mangile, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mitigasi merupakan serangkaian upaya yang dilakukan untuk mengurangi risiko bencana baik melalui pembangunan fisik, maupun penyadaran dan peningkatan kemampuan menghadapi ancaman bencana (Faturahman, 2021). Hasil penelitian ini sejalan dengan penelitian Yusuf & Mangile (2019), yang menyatakan bahwa tingkat pengetahuan kepala keluarga sebelum diberikan penyuluhan tingkat pengetahuan berada di kategori kurang yaitu 8 orang, kategori cukup 21 orang, dan kategori baik 1 orang, dengan nilai rata-rata secara keseluruhan yaitu 8,20. Berdasarkan data ini, data responden yang memiliki tingkat pengetahuan dalam kategori baik hanya 1 orang, hal ini menunjukan bahwa tingkat pengetahuan kepala keluarga tentang kesiapsiagaan bencana banjir masih bisa dibilang sangat terbatas.…”
Section: Pembahasan Tingkat Pengetahuan Warga Tentang Mitigasi Bencan...unclassified
“…Some finding reveals that it is significantly different between the people who have joined extension activity rather than the people who have not involved in extension. When the people join, it can jump the level of their knowledge instead of before they mix in extension activity (Yusuf & Kurnia Mangile, 2019).…”
Section: Figure 1 Percentage Of Community Participation In Disaster and Environmental Extension Activitiesmentioning
confidence: 99%